Respostas
respondido por:
3
Coletando os dados da P.A., temos:
a1= -3 .:. An=113 .:. r=a2-a1 r=1-(-3) r=4 e n=?
Aplicando a fórmula do termo geral da P.A., temos:
An=a1+(n-1)r
113= -3+(n-1)4
113+3=4n-4
116 = 4n-4
116+4=4n
120=4n
n=120/4
n=30
a1= -3 .:. An=113 .:. r=a2-a1 r=1-(-3) r=4 e n=?
Aplicando a fórmula do termo geral da P.A., temos:
An=a1+(n-1)r
113= -3+(n-1)4
113+3=4n-4
116 = 4n-4
116+4=4n
120=4n
n=120/4
n=30
ImeloOfc:
espero ter ajudado!
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás